2014
DOI: 10.1021/ja508329c
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Based Growth of Polymeric Carbon Nitride Layers and Their Use in a Mesostructured Polymer Solar Cell with Voc Exceeding 1 V

Abstract: Herein we report a general liquid-mediated pathway for the growth of continuous polymeric carbon nitride (C3N4) thin films. The deposition method consists of the use of supramolecular complexes that transform to the liquid state before direct thermal condensation into C3N4 solid films. The resulting films exhibit continuous porous C3N4 networks on various substrates. Moreover, the optical absorption can be easily tuned to cover the solar spectrum by the insertion of an additional molecule into the starting com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
187
0
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 232 publications
(202 citation statements)
references
References 30 publications
2
187
0
13
Order By: Relevance
“…They have been used in a wide range of photocatalytic applications, especially for solar water-splitting, [1][2][3][4][5][6][7] as well as in photovoltaics, as tunable yellow phosphors and fl uorescent markers for bioimaging. [8][9][10][11][12] Despite the large variety of reported synthesis routes and substantial progress in characterization of the materials, the nature of charge transport in CN has not been unveiled to date. While early work suggested a band structure typical for inorganic semiconductors, [ 1 ] subsequent investigations showed that the optical properties are closely connected to the heptazine monomer.…”
Section: Doi: 101002/adma201503448mentioning
confidence: 99%
“…They have been used in a wide range of photocatalytic applications, especially for solar water-splitting, [1][2][3][4][5][6][7] as well as in photovoltaics, as tunable yellow phosphors and fl uorescent markers for bioimaging. [8][9][10][11][12] Despite the large variety of reported synthesis routes and substantial progress in characterization of the materials, the nature of charge transport in CN has not been unveiled to date. While early work suggested a band structure typical for inorganic semiconductors, [ 1 ] subsequent investigations showed that the optical properties are closely connected to the heptazine monomer.…”
Section: Doi: 101002/adma201503448mentioning
confidence: 99%
“…[9] We also showed the power of this method by using ac omplex with phenyl-substituted triazines to grow modified CN thin films as the active layers in solar cells and light-emitting diodes, [10] applications that rely on the control of the band structure and the emission properties.…”
mentioning
confidence: 99%
“…For the electrochemical or photoelectrochemical applications, including water electrosplitting, fuel cells, and solar cells, a direct and continuous g-C 3 N 4 layer is preferred. Recently, numerous studies have been devoted to the synthesis of a g-C 3 N 4 thin lm, including bubble template method, 11,12 sol-gel techniques, 13 chemical exfoliation method, 14 deposition method, 15,16 as well as spin-coating method. 17 It was recognized that the photocatalytic activity of g-C 3 N 4 is limited by its high recombination probability of photogenerated electron-hole pairs.…”
Section: -10mentioning
confidence: 99%
“…The precursor powder was prepared by a concussion-hybrid method and the lm electrodes were afforded by liquid-based growth reaction, as described by Xu et al 15 In a typical process, 4 g of a mixture of cyanuric acid and benzoguanamine (molar ratio of 1 : 1) and the required amount of AgNO 3 were dispersed in 40 mL deionized water and stirred continuously for 6 hours. The white suspension was then centrifuged at about 7500 rpm and the sediment was freeze-dried for 24 h.…”
Section: Preparation Of the Lm Electrodementioning
confidence: 99%